Solid-state fermentation of sweet potato using two monoculture fungi: changes in protein, fatty acid and mineral composition (1997)
This study evaluated the protein fatty acid and mineral changes in sweet potato root heal inoculated with two selected fungi by solid state fermentation procedure. The total protein content was raised from 4.95% to 11.83% and 6.69% within 48 hrs for Aspergillus oryzae and Aspergillus niger respectively. The total lipid dropped from 1.93% in the control to 1.36 and 4.19% for A. niger and A. oryzae respectively. The fatty acids C16:0 andC18:2 were preponderant over other fatty acids with A. niger and A. oryzae recording 18.94 and 28.17% for 06:0 and 43.20 and 37.88% for C18:2 respectively. The ash content values were 3.53% for the control, 3.54 and 4.51% for A. niger and A. oryzae respectively. The mineral changes analysed were for Calcium. Potassium, Iran. Manganese, Sodium, Zinc and Phosphorus. The pH changed from 5.26 for the control to 3.80 and 5.39 for A: niger and A oryzae respectively